KONSEP PURDAH PRESPEKTIF RIFFAT HASSAN - Nur Iftitahul Husniyah (Akademika, 2018)
Abstract: Purdah has become a Muslim institution for a thousand years. Purdah is an integral part of medieval Muslim society and culture. The concept of purdah stems from the system of dividing two regions in Islamic society, namely the private area (home) and the public area (workplace). Women are in a private area while men are in public areas. According to the general assumption of Islamic society, as long as women are in the public area, women must wear a veil or purdah. Based on the general concept, according to Riffat Hassan about the concept that women do not have to cover their faces with a veil when they leave home. Riffat interprets the hijab (including headscarves or purdah) does not meant to have clothes that cover the entire body of a woman including her face and palms, but clothes that are according to socially properness.Keywords: Purdah, Riffat Hassan.